Adaptive NKG2C+CD57+ Natural Killer Cell and Tim-3 Expression During Viral Infections - Kared, Hassen; Martelli, Serena; Tan, Shu Wen; Simoni, Yannick; Chong, Meng Li; Yap, Siew Hwei; Newell, Evan W.; Pender, Sylvia L. F.; Kamarulzaman, Adeeba; Rajasuriar, Reena; Larbi, Anis (Frontiers in Immunology, 2018)
Repetitive stimulation by persistent pathogens such as HCMV or HIV induces the differentiation of NK cells. This maturation pathway is characterized by the acquisition of phenotypic markers, CD2, CD57 and NKG2C, and effector functions – a process regulated by Tim-3 and orchestrated by a complex network of transcriptional factors, involving T-bet, Eomes, Zeb2, PLZF, and Foxo3. Here, we show that persistent immune activation during chronic viral co-infections (HCMV, HCV, HIV) interferes with the functional phenotype of NK cells by modulating the Tim-3 pathway; a decrease in Tim-3 expression combined with the acquisition of inhibitory receptors skewed NK cells toward an exhausted and cytotoxic phenotype in an inflammatory environment during chronic HIV infection. A better understanding of the mechanisms underlying NK cell differentiation could aid the identification of new immunological targets for checkpoint blockade therapies in a manner that is relevant to chronic infection and cancer.